# math

posted by .

Need help in solving these
Problem #1

For f(x)=-6x3+10

find f(4) and f(-4)

Problem #2

For g(x)=20-5x2

find f(1) and f(-1)

• math -

Online "^" is used to indicate an exponent.

f(x) = -6x^3 + 10

F(4) = (-6 * 4 * 4 * 4) + 10

f(-4) = (-6 * -4 * -4 * -4) + 10

I'll let you do the calculations.

In the second problem, there is no difference, since a negative times a negative is a positive.

## Similar Questions

1. ### lattice math

Why should we estimate before solving a problem?
2. ### math

I tried many times this problem but it makes nonsense. Which statement is NOT true?
3. ### beginning chemistry

The problem says indicate the the number of sig. figs. that should be present in the answers to the following problem without solving the problem. 0.70 x 7.00 x 6.880= What is a sig.fig. and how can you find them without solving the …
4. ### College Math II

Solve the problem. If a manufacturer charges q dollars each for footballs, then he can sell 3000 – 150q footballs per week. Find the polynomial R(q) that represents the revenue for one week. Find the weekly revenue if the price is …
5. ### math

What strategy did you use in solving this problem?
6. ### math

Hi I need help with this math problem: The plane that contains the points (8,3,1), (2,6,3), and (4,6,2) has an equation of the form ax + by + cz = d. Find coefficients for this equation, trying two different approaches to the problem. …
7. ### Math

I need help in solving this: Problem #1 For f(x)=-6x3+10 find f(4) and f(-4) Problem #2 For g(x)=20-5x2 find f(1) and f(-1)
8. ### math

Please need help on this Create an equation of a nonlinear function and provide two inputs for your classmates to evaluate. f(x)=10²+5 find f(2) and f(-2) --------------------------------------------------------------------------------------------------------------------- …
9. ### Algebra 2

We have opposing answers, can you help? What is the simplified form of (2x2 + 4x – 3)(3x + 1) ?
10. ### Composition of Functions

1. Find (f·g)(x) where f(x) = 1/x²+3 and g(x) = √x-2. a) (f·g)(x) = 1/x-2 b) (f·g)(x) = 1/√x-2 +3 c) (f·g)(x) = √-2x²-5/x²+3 2. Find (g·f)(x) where f(x) = x²-2 and g(x) = 5x-8. a) (g·f)(x) = 5x²-18 b) (g·f)(x) = 5x²-4 …

More Similar Questions